2018
DOI: 10.1074/mcp.ra117.000519
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects of Combined Birinapant and Paclitaxel on Pancreatic Cancer Cells Investigated via Large-Scale, Ion-Current-Based Quantitative Proteomics (IonStar)

Abstract: SummaryDespite decades of effort, pancreatic adenocarcinoma (PDAC) remains an intractable clinical challenge.An insufficient understanding of mechanisms underlying tumor cell responses to chemotherapy contributes significantly to the lack of effective treatment regimens. Here, paclitaxel, a first-line chemotherapeutic agent, was observed to interact synergistically with birinapant, a Second Mitochondrial-derived Activator of Caspases mimetic. Therefore, we investigated molecular-level drug interaction mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…Blue dots predominate over the red, suggesting an overall synergistic interaction that was confirmed quantitatively by model analysis. This figure is reproduced with permission of the American Society for Biochemistry and Molecular Biology, from Wang et al wileyonlinelibrary.com]…”
Section: Quantification Methods For Pd Ddismentioning
confidence: 99%
See 1 more Smart Citation
“…Blue dots predominate over the red, suggesting an overall synergistic interaction that was confirmed quantitatively by model analysis. This figure is reproduced with permission of the American Society for Biochemistry and Molecular Biology, from Wang et al wileyonlinelibrary.com]…”
Section: Quantification Methods For Pd Ddismentioning
confidence: 99%
“…Traditional chemotherapeutic agents that are not molecularly targeted to specific effector pathways tend to be promiscuous; they often exhibit nonspecific pharmacological effects, which further complicates the prediction of PD DDIs based on first principles. However, ‘omics technologies combined with bioinformatics hold the potential for providing new insights into mechanisms of drug action, and PD DDI studies at a detailed molecular level can reveal new targets or pathways underlying the effects of established drugs …”
Section: The Need For Pd Ddi Studiesmentioning
confidence: 99%
“…The peptide fragments derived from purified human FAK were subjected to HCD MS/MS analysis as previously described 29, 48, 49. The nano-flow reverse phase LC included a Spark Endurance autosampler (Emmen, Holland) and an ultra-high pressure Dionex (Sunnyvale, CA) ultimate Nano-2D Ultra capillary/nano-LC system.…”
Section: Methodsmentioning
confidence: 99%
“…Alteration of other post-translational modifications other than tyrosine phosphorylation was not analysed. Large scale proteomics analysing the temporal effects of paclitaxel on pancreatic cancer cells, highlighted the role of proteins involved in mitochondrial function, survival (PI3K pathway) and cell cycle arrest in a key resistance mechanism [ 56 ]. Proteomics has identified that several negative feedback mechanisms are relieved upon mTORC1 inhibition, thus explaining the disappointing results from clinical trials on this target [ 38 , 39 , 57 , 59 ].…”
Section: Introductionmentioning
confidence: 99%